2015
DOI: 10.3233/nre-141186
|View full text |Cite
|
Sign up to set email alerts
|

The ICF as a framework to collect and interpret data on the extent and variety of disability in neurological conditions

Abstract: INTRODUCTION: Neurological conditions are associated with high levels of disability. OBJECTIVES: The aim of this study was to describe, using the International Classification of Functioning, Disability and Health (ICF), the most relevant aspects of disability in patients with neurological conditions. We collated data from previous studies on myasthenia gravis, migraine, Parkinson's disease, multiple sclerosis, traumatic brain injury, stroke, epilepsy, vegetative state and minimally conscious state, and identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 13 publications
0
19
0
4
Order By: Relevance
“…These factors may have a negative impact on patients' psychosocial and spiritual dimensions and are associated with ideas of finitude of life, frequently leading to existential issues. QoL gradually decreases, whereas the burden on patients and family caregivers increases . Results following assessment with the Palliative Outcome Scale suggest that PD patients have moderate palliative care needs .…”
Section: Does Parkinson's Disease Fit Into the Palliative Care Scope?mentioning
confidence: 99%
See 1 more Smart Citation
“…These factors may have a negative impact on patients' psychosocial and spiritual dimensions and are associated with ideas of finitude of life, frequently leading to existential issues. QoL gradually decreases, whereas the burden on patients and family caregivers increases . Results following assessment with the Palliative Outcome Scale suggest that PD patients have moderate palliative care needs .…”
Section: Does Parkinson's Disease Fit Into the Palliative Care Scope?mentioning
confidence: 99%
“…QoL gradually decreases, whereas the burden on patients and family caregivers increases. [9][10][11] Results following assessment with the Palliative Outcome Scale suggest that PD patients have moderate palliative care needs. 12 Problems that are most frequently scored as severe or overwhelming include walking problems, pain, problems using the arms and hands, difficulties in communicating, fatigue, drooling, constipation, sleeping problems, and falls.…”
mentioning
confidence: 99%
“…Seizures in children and adults might encompass several disabling health conditions and have important practical implications for managing rehabilitation. It is important for rehabilitation professionals to study the effects of interventions on functioning, relevant disability, and quality of life as major areas of their focus 15 . It is suggested that epilepsy may be associated with a variety of functioning problems as defined in the International Classification of Functioning, Disability and Health, 16 such as attention, emotional, and seeing functions in the body functions component; and watching, problem‐solving, fine hand use, walking, self‐care activities, relationships, community life, and recreation and leisure in the activities and participation component 15 .…”
Section: Clobazam Monotherapy For Focal or Generalized Seizures1mentioning
confidence: 99%
“…The World Health Organization's International Classification of Functioning, Disability, and Health (ICF) 16 provided a comprehensive, multidisciplinary, bio-psychosocial model of functioning and disability, and has been previously used to describe neurological trauma in both acute and chronic phases. 17,18 The value of the ICF in interprofessional practice and research has gained international recognition. It has demonstrated strengths in the promotion of a comprehensive perspective on health, ease in the application of this theory to practice, and the ability to enhance communication and collaboration across HCPs.…”
Section: The International Classification Of Functioning Disability Amentioning
confidence: 99%